Subchondral Cellular Density Decreases with Increasing Grade of Cartilage Degeneration in Knee Osteoarthritis – An Ex vivo Histopathological Analysis - Sathish Muthu; Ragavi Kandasamy; Suryaprabha Palanisamy; Arun Anand Palaniappan (Journal of Orthopaedic Case Reports)
Introduction: Subchondral milieu has been the region of interest in recent clinical trials demonstrating it as an effective treatment focus in knee osteoarthritis (OA). However, a systematic analysis of the subchondral cell population density is lacking in knee OA. Hence, this study aims to analyze the cell population density of the subchondral zone for every stage of cartilage degeneration to analyze the rationale behind this evolving treatment method for knee OA. Materials and Methods: This is an ex vivo histopathological analysis of the distal femur and proximal tibia articular specimens from the patients undergoing total knee replacement for primary knee OA between November 2023 and March 2024. Two pathologists independently graded and analyzed the subchondral cell density based on the International Cartilage Repair Society cartilage injury grading system. Results: We noted a significant association between the grade of cartilage degeneration and the subchondral cell density (r = 0.831, P < 0.001). We noted a statistically significant decrease in the cell density for every stage of cartilage injury compared to the control (P < 0.001). We also noted a significant decrease in cell density between the early and late stages of cartilage degeneration (P < 0.001). We did not note any significant difference in the cell density between the tibial and femoral articular cartilage for every grade of cartilage degeneration analyzed (P = 0.432). Conclusion: Subchondral cell density decreases significantly with increasing grade of degeneration in knee OA. Subchondral milieu warrants attention to be considered as a potential treatment focus that could alter the disease progression in knee OA.